ACTUAL ANALYSIS OF UZBEKISTAN’S STOCK MARKET: PROBLEM, SOLUTION AND SUGGESTIONS - Butaev Javlon Inatillo o‘g‘li (American Journals, 2023)
In this article, the development of all branches and sectors of the economy requires the harmonious development of the real sector and the financial sector. In this, the development of the country’s economy is directly related to the stock market, and the analysis of the modern state of the stock market of Uzbekistan and developed countries was carried out a number of scientific proposals and practical recommendations were given on the creation of economic conditions and the further improvement of the stock market, and opinions of foreign and local scientists were presented on this topic.
Keywords: stock market, capital market, investor, capitalization, depositor, issuer, share, bond, joint stock company.